Écrire et intervenir en scientifique queer de couleur : une épopée des réseaux - Marc Jahjah (Genre, Sexualité et Société)
How can we make our voices, experiences and work exist, and how can we bring those of the most vulnerable into public, political and media spaces that are hostile to queer scientists of colour? This article sketches out a number of avenues, linking theory, narrative, ethnography, fiction, poetry and the literary arts to discover new personal and collective resources. By moving from one place to another, they will lead us to broaden our scope, to move from situated enquiry to taking into account all the voices – Including the dead – that populate us, overwhelm us and demand that we collectively do them justice.